La Asamblea Constituyente y la democracia en riesgo: corporativismo, rentismo y capitalismo político como pilares de la nueva Constitución boliviana - Ayo, Diego (2014)
Did the new Bolivian Constitution of 2009 influence a change on its democratic model? The thesis of the article claims that as a result of how the Constitution elaboration process was carried out on a frame of certain historical conditions, the product elaborated –The Constitution- by the Constituent Assembly had little substantial change in contrast to former Constitutions. Historical constrains of the Bolivian economy and the polarization of the actors involved on the elaboration process of the new Constitution had a great influence to prevent a substantially different new one. Progressive’s elements were introduced as a matter of result of the Bolivian revolution as Human Rights, Plurinationality, and Regional Autonomies, but certain constitutional prerogatives remained unchanged to preserve the status quo. The presence of corporatists, rentist and statist actors has been a trend along Bolivian history, which does allow the reproduction of the internal political relationships of the Bolivian model and inhibits the possibility of a substantial change or re-foundation. Furthermore, the pos-contitutional situation will consolidate a democracy that hardly would break the historical constrains thatrules its hybrid character.